An unusual cause of ventricular tachycardia: Port-A-Cath fracture and embolization into the pulmonary artery - Wassef, Anthony W.A. (Heart Int, 2014)
We describe the case of a patient with a previously placed Port-A-Cath who was admitted to hospital for new onset of non-flushing catheter and palpitations with ventricular tachycardia. A chest X-ray and a linogram showed a Port-A-Cath fracture and distal embolization into the right ventricle resulting in ventricular tachycardia. The catheter was removed percutaneously using a Goose Neck snare with no complications and resolution of the ventricular tachycardia. The removed segment demonstrated thrombus. Prompt removal of the embolized catheter fragments should be undertaken given the subtle nature of the embolization and the potential complications.